An Analysis of the Criminal Act of Granting Business Permits by Officials Without Completed Environmental Permits - Gustika Sandra; Tarmizi; Jumra; Rika Damayanti; Muh. Bakri; Asia A. Pananrangi; Mukhawas Rasyid; A. Arfyan Pratama; Sakti Yadi (IJCS: International Journal of Community Service, 2022)
Between humans and their environment there is a dynamic relationship. Changes in the living environment will cause changes in the physical and psychological conditions of humans to adapt to new conditions. Changes in the human condition will in turn cause changes in the environment. Thus, it can be said that not only the environment can affect humans, but humans can also be the main and dominant factor influencing the environment, so that human awareness is needed for their own environment. This is done in order to obtain a good environment and in accordance with human needs, so that the dynamic relationship between humans and their environment will be maintained. The method of this community service is the counseling method in the form of direct presentation of lecture material to 5 respondents using leaflets and browser media. This community service as a whole is very effective, so that an increase in knowledge is obtained after counseling on the Criminal Act of Granting Business Permits by Officials Without Completed Environmental Permits.